DIGITAL HUMANITIES – HUMANIORAS FREMTID? - Porsdam, Helle; Rendix, Mia (K&K - Kultur og Klasse, 2013)
DIGITAL HUMANITIES: THE FUTURE OF THE HUMANITIES | The article deals with a widespread global phenomen within the Humanities, i.e. Digital Humanities. In the wake of the spread of the Internet with opportunities for sharing knowledge, open access, and the World Wide Web as a democratic agency, the Humanities faculties are in the process of adapting themselves to exploiting digital challenges and potentials. Much has been written on digitalization’s ideological and tech nological aspects and consequences, but researchers from the Humanities first began over the past five to seven years to devise ways in which new Digital Humanities should be formed. Special centers for Digital Humanities already exist at leading American and British universities, and several specific manifests on the digitalization of the Humanities have been written. The authors of this article wish to discuss and problematize the Digital Humanities in both an international and national context, and the consequences of Digital Humanities that we see for the actual role of research and the potential for acknowledgement.